Material of the Climate change, agriculture and food security masterclasses for FCDO advisors - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
In the context of UK’s Presidency of COP26, with a focus on nature and sustainable agriculture, CCAFS and FCDO developed this Learning Journey, which aimed to enhance capacity amongst FCDO advisers to support design, implementation and performance assessment of climate-smart agriculture (CSA) projects and programmes.